2019
DOI: 10.1088/1748-9326/ab10a8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing landscape potential for human sustainability and ‘attractiveness’ across Asian Russia in a warmer 21st century

Abstract: In the past, human migrations have been associated with climate change. As our civilizations developed, humans depended less on the environment, in particular on climate, because technological and economic development in the span of human history allowed us to adapt to and overcome environmental discomfort. Asian Russia (east of the Urals to the Pacific) is known to be sparsely populated. The population is concentrated along the forest-steppe in the south, with its comfortable climate and thriving agriculture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
0
7
0
2
Order By: Relevance
“…Archard et al (2008) estimated 65 % of all forest fires in the Russian Federation were caused by human ignition, and a more recent study found approximately half of all fires in the Sakha Republic are caused by anthropogenic activities (Kirillina et al, 2020). Throughout boreal Canada, anthropogenic factors increase fire probabil-ity (Parisien et al, 2016), with humans igniting most fires close to roads while lightning-caused fires are responsible for the majority of burned area in the more remote locations (Gralewicz et al, 2012). Blouin et al (2016) found that 45 % of wildfires in Alberta were started by lightning but were responsible for 71 % of burned area.…”
Section: Lack Of Agreement Between Official Statistics and Satellite Observationsmentioning
confidence: 99%
“…Archard et al (2008) estimated 65 % of all forest fires in the Russian Federation were caused by human ignition, and a more recent study found approximately half of all fires in the Sakha Republic are caused by anthropogenic activities (Kirillina et al, 2020). Throughout boreal Canada, anthropogenic factors increase fire probabil-ity (Parisien et al, 2016), with humans igniting most fires close to roads while lightning-caused fires are responsible for the majority of burned area in the more remote locations (Gralewicz et al, 2012). Blouin et al (2016) found that 45 % of wildfires in Alberta were started by lightning but were responsible for 71 % of burned area.…”
Section: Lack Of Agreement Between Official Statistics and Satellite Observationsmentioning
confidence: 99%
“…However, Scots pine may break through further north up, to 70 • N, along the broad valleys of the big Siberian rivers, the Yenisei and the Lena, in eastern Siberia, where a deeper active layer thaws in the summer, allowing for Scots pine to succeed [25]. The permafrost border distribution across Russia was calculated using growing GDD 5 , NDD, and annual precipitation (R 2 = 0.78), as was also the case with our bioclimatic Siberian vegetation model [26,27]. Seed mass was predicted within the potential P. sylvestris range and was overlapped with the permafrost border to separate actual and non-realized (north-eastwards of the border) seed zones in both contemporary and future climates.…”
Section: Climate Datamentioning
confidence: 99%
“…Може се рећи да је међународна заједница сажела проблем еколошких криза у три сегмента: 1. превенција и спречавање даље деградације животне средине и очување природних ресурса; 2. санација и развој области угрожених еколошким катастрофама и 3. спречавање и решавање сукоба као последица недостатка ресурса и њихове трајне деградације. Научна предвиђања промена у животној средини и последица миграција људи су од суштинског значаја за развој стратегија за дугорочно економско планирање и друштвени развој, као и постизање благостања и просперитета (Parfenova et al, 2019).…”
Section: уводunclassified